2016
DOI: 10.11648/j.sjph.20160401.20
|View full text |Cite
|
Sign up to set email alerts
|

Validation of YPAS-PT – The Yale Physical Activity Survey for Portuguese Older People

Abstract: Abstract:This study aimed to translate, adapt and validate the Yale Physical Activity Survey (YPAS) to Portuguese culture in order to assess the level of physical activity in a country with one of the world's highest percentage of senior citizens. Permission was obtained from the original authors and translated according to WHO guidelines. Validation included 471 older adults (70.3% women; 74.9±6.5 years), covering Criterion Validity, through Spearman's rho, with a cross-reference standard, by accelerometry wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 28 publications
3
17
0
1
Order By: Relevance
“…During some household activities, acceleration is low, which decreases the physical activity estimated by the accelerometer [28]. Moreover, in the study of Machado et al [29], it was suggested that Freedson's energy expenditure algorithm, that was used in our study, is not sensitive to low-intensity activity measurements. Considering that older adults are characterized by mainly low-intensity activities, this could be another potential explanation of the low association between the results received by PAQE-PL and the accelerometer scores.…”
Section: Discussionmentioning
confidence: 70%
“…During some household activities, acceleration is low, which decreases the physical activity estimated by the accelerometer [28]. Moreover, in the study of Machado et al [29], it was suggested that Freedson's energy expenditure algorithm, that was used in our study, is not sensitive to low-intensity activity measurements. Considering that older adults are characterized by mainly low-intensity activities, this could be another potential explanation of the low association between the results received by PAQE-PL and the accelerometer scores.…”
Section: Discussionmentioning
confidence: 70%
“…PA profiles were also evaluated by a short version of “Yale Physical Activity Survey” (YPAS), validated for the Portuguese population, 28 which defines six distinct PA dimensions: 1) vigorous activity, 2) leisurely walking, 3) moving, 4) standing, and 5) sitting, and a PA total score, considering a typical week. Both questionnaires were administered by face-to-face interviews involving the same trained examiners.…”
Section: Methodsmentioning
confidence: 99%
“…Participants completed a study specific questionnaire covering basic demographics, general health, falls and foot pain. They also independently completed the Yale Physical Activity Survey for Older People 21,22 ; Foot and Ankle Outcome Score (FAOS) 23,24 ; Falls Efficacy International (FES-I) 25,26 ; Activities-specific Balance Confidence (ABC) Scale 27,28 ; a single question on whether they had pain in either foot (yes/ no) 29 ; and Foot pain severity (each foot separately) was measured with a 100 mm visual VAS 30,31 .…”
Section: Assessment Outcomesmentioning
confidence: 99%